2005
DOI: 10.1002/cncr.21298
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and prevalence of BRCA1 and BRCA2 germline mutations in Sardinian patients with breast carcinoma through hospital‐based screening

Abstract: BACKGROUND.Factors that are predictive of carrying BRCA1 and BRCA2 germline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
3
22
0
1
Order By: Relevance
“…However, this frequency is in line with other Italian population studies [6][7][8][9]. Furthermore, many of our BRCA1/2 mutations have previously been reported to be either neutral or of unknown function, and for this reason less than 10% of HBOC families who were carriers of a deleterious BRCA1/2 mutation could be given an accurate estimate of their familial risk.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, this frequency is in line with other Italian population studies [6][7][8][9]. Furthermore, many of our BRCA1/2 mutations have previously been reported to be either neutral or of unknown function, and for this reason less than 10% of HBOC families who were carriers of a deleterious BRCA1/2 mutation could be given an accurate estimate of their familial risk.…”
Section: Resultssupporting
confidence: 78%
“…Those meeting the stringent family selection criteria for HBOC were then tested for the presence of BRCA1/2 mutations. Several recent studies have summarized the genetic alterations in hereditary breast cancer for different regional Italian populations [6][7][8][9]. Here we report on the prevalence of BRCA1/2 germline mutations in HBOC families in North-Central Italy.…”
Section: Introductionmentioning
confidence: 92%
“…Mutation (917delTT) was first described in two unrelated French families (Muller et al, 2004), then it was reported in Spain (John et al, 2007) and in Italy (Palomba et al, 2005). This mutation was also found in four Algerian families (Uhrhammer et al, 2008;Cherbal et al, 2010), three unrelated Tunisian families (Mahfoudh et al, 2011) and recently in a Moroccan patients (Tazzite et al, 2012;Laraqui et al, 2013) .…”
Section: C798_799delttmentioning
confidence: 88%
“…In Sweden, 34% of high-risk families carry BRCA1 mutations, but only 2% carry BRCA2 mutations 46 . By contrast, 32% of high-risk Sardinian families carry mutations in BRCA2, and 11%, mutations in BRCA1 47 . Interestingly, dna microarray and immunohistochemical analyses revealed that 80%-90% of breast cancers in women with germ-line mutations in BRCA1 are triple-negative (er-, pgr-, her2-) 26,48-52 .…”
Section: Triple-negative and Brca-mutant Tumour Cellsmentioning
confidence: 94%